Analysis of Cybersecurity Implementation in Indonesia Based on the Framework of Administrative Law - Tobondo, Yuyun Alfasius; Juliana, Sanny Feria; Ruagadi, Henry Anderson; Tondowala, Sulvia Fery Hanry; Ngguna, Yakin (Fakultas Ekonomi Universitas KristenTentena, 2024)
This study analyzes the application of administrative law in enhancing cybersecurity in Indonesia, evaluates data protection policies within this context, and identifies challenges and opportunities in implementing cy-bersecurity in the Society 5.0 era. Utilizing the Literature Review method, this research integrates results from various studies to provide a robust quantitative estimate of the effects of exist-ing regulations. The data derives from primary and secondary literature, including books, journals, and scientific research. Findings indicate that despite existing regulations, the implementation and enforcement remain inadequate, as evidenced by frequent data breaches across various sec-tors. This research significantly contributes to the literature on the rela-tionship between administrative law and cybersecurity, as well as per-sonal data protection in the digital era. However, this study's limitations include its reliance on existing literature, with limited attention to the technical aspects of cybersecurity. Future research should combine technical and policy approaches to develop more comprehensive cyber-security solutions.